When Is Proactivity Wise? A Review of Factors That Influence the Individual Outcomes of Proactive Behavior - Parker, Sharon; Wang, Y.; Liao, J. (2019)
There is solid evidence that proactivity, defined as self-initiated and future-focused action to change oneself or the situation, can positively benefit individuals and organizations. However, this way of behaving can sometimes be ineffective or have negative consequences. We seek to understand what factors shape the effect of proactivity on individual-level outcomes. On the basis of a review of 95 articles, we identify three categories of factors that mitigate or exacerbate the effectiveness of proactive behavior: task and strategic considerations (e.g., situational judgment), social and relational considerations (e.g., having an open leader), and self-regulatory considerations (e.g., learning orientation). We then extrapolate from this review, and draw on psychological theories of wisdom, to suggest that individuals can be more or less "wise" in the proactive goals they set, and in how they pursue those goals. In closing, we identify further research directions that flow from the notion of wise proactivity.